The use of authentic materials in online English teaching: from the learners' perspective - Raihan, Gufron; Md Zamin, Ainul Azmin (Department of English Education, Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
The main objective of this study is to explore students' views on English teaching using authentic materials. This research was conducted in an English class where the students are staffs who are lecturers in a private university in Jakarta. An inductive qualitative research method was employed by interviewing five randomly selected respondents after teaching for 15 weeks. The data from the interview were analyzed in three steps; quotation, coding, and thematic analysis using Atlas.ti. The data analysis results showed that using authentic materials was more interesting and impressive than the ones that were not authentic and not related to the students' subject matter. Using authentic material also increases students' interest in speaking more because the topics discussed are related to students' real world. Besides, this method can increase interest in reading because students are familiar with vocabularies that are related to their majors. However, this method is not suitable for applying in a classroom where students are from different majors